Mazhab Syafi'i di Malaysia: Sejarah, Realiti dan Prospek Masa Depan - Haji Abd. Majid, Mahmood Zuhdi (Jurnal Fiqh, 2007)
Although the Shafi'ite School came later compared to any other schools of Fiqh, it was easily accepted among the people and rulers of the country. Its moderateness could have been the factor because by nature the Malays are themselves moderate in their daily practices. However, in due history, the Malays began to experience changes from time to time and became more complex and there was a feeling that not all of the Shafi'ite views could appropriately accommodate with the changes. In this process of modernization and reformation, there were those who were inclined to accept other schools of thought. Weaknesses in the traditional practices based on the Shafite Fiqh need to be overcome. Novel ideas were considered and there were some would prefer to return to the original principles of the school and manifest them in accordance with the contemporary needs and local circumstances.